Population Dynamics of Major Sucking Pests of Mung bean in Western Rajasthan and Their Management Using Newer Insecticides: POPULATION DYNAMICS OF MUNG BEAN SUCKING PEST - Dindayal Tanwar; M M Kumawat; M M Sundria; Dama Ram (Annals of Arid Zone, 2024)
A field experiment was conducted to study the seasonal incidence of major insect pests of mung bean [Vigna radiata (L.) Wilczek] under arid conditions of Rajasthan. A total of ten treatments were used to evaluate the bio-efficacy of insecticides against three sucking pests viz. leafhopper (Empoasca kerri Pruthi), whitefly (Bemisia tabaci (Genn.) and thrips [Caliothrips indicus (Bagnall)]. The incidence of leafhopper, whitefly and thrips began on mung bean in the second week of August peaked in the September, gradually declined thereafter. There was negative significant correlation between leafhoppers and maximum temperature, positive non-significant with whitefly and positive significant correlation between thrips and maximum temperature. Relative humidity showed positive significant correlation with leafhopper and positive non-significant with whitefly and thrips. Out of nine insecticides the standard check of Dimethoate 30 EC was found most effective against population of leafhopper, whitefly and thrips followed by thiamethoxam 25 WG and fipronil 5 SC. Lambda-cyhalothrin 17.8 SL, Metarhizium anisopliae 1.15 WP as well as Beauveria bassiana 1.15 WP ranked as less effective treatments against leafhoppers, whitefly and thrips. The maximum yield was recorded in the plots treated with thiamethoxam 25 WG. The highest benefit cost ratio was obtained with dimethoate 30 EC followed by thiamethoxam 25 WG, while lowest benefit cost ratio was computed in the plots treated with Beauveria bassiana and Metarhizium anisopliae